2015
DOI: 10.1002/ptr.5548
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Black Tea Consumption on Intracellular Cytokines, Regulatory T Cells and Metabolic Biomarkers in Type 2 Diabetes Patients

Abstract: The present study was undertaken to evaluate the effects of black tea intake on inflammatory cytokines and metabolic biomarkers in Type 2 diabetes mellitus (T2DM). Thirty patients with T2DM were randomly assigned either to a High Intake (HI) group, consuming three cups (600 mL) of black tea per day; and a Low Intake (LI) group, administered 1 cup (200 mL) per day, each during a 12-week period. Intracellular cytokine expression, regulatory T cells (Treg), glycemic and lipid profiles were measured at baseline an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 41 publications
0
27
0
1
Order By: Relevance
“…Since the completion of this meta-analysis, additional RCTs investigating the effects of tea or cocoa products containing flavanols on lipid and anthropometric variables have been added to the existing literature [111,169,170,171,172,173,174,175,176,177,178,179,180,181,182,183]. The heterogeneity of these trials remains high with population samples including mixed sexes and ages, obese, overweight, healthy, hyperlipidemic and/or diabetic subjects, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Since the completion of this meta-analysis, additional RCTs investigating the effects of tea or cocoa products containing flavanols on lipid and anthropometric variables have been added to the existing literature [111,169,170,171,172,173,174,175,176,177,178,179,180,181,182,183]. The heterogeneity of these trials remains high with population samples including mixed sexes and ages, obese, overweight, healthy, hyperlipidemic and/or diabetic subjects, etc.…”
Section: Discussionmentioning
confidence: 99%
“…et al, 2010). Likewise, the administration of 3 cups/day (600 mL, high intake) or one cup/day (200 mL, low intake) of black tea to 36 patients with T2D (18 men and 18 women) for 12 weeks showed certain improvements related to the disease in the high-intake-patients (Mahmoud, F. et al, 2016). Thus, in the tea-group it was observed reduced HbA1c and total serum cholesterol levels, along with increased regulatory T cells CD3+ CD4+ CD25+ FOXP3, CD3+ CD4+ IL-10+ cells (an immunosuppressive phenotype), reduced (pro-inflammatory) CD3+ CD4+ IL-17+ cells and reduced Th1-associated CD3+ CD4+ IFN-γ+ cells.…”
Section: 1-teamentioning
confidence: 99%
“…Thus, in the tea-group it was observed reduced HbA1c and total serum cholesterol levels, along with increased regulatory T cells CD3+ CD4+ CD25+ FOXP3, CD3+ CD4+ IL-10+ cells (an immunosuppressive phenotype), reduced (pro-inflammatory) CD3+ CD4+ IL-17+ cells and reduced Th1-associated CD3+ CD4+ IFN-γ+ cells. The preparation of tea was as follows: one tea bag as (2.5 g) of dry black tea as sold was infused in 200 mL of water brought to a boil, then steeped for 3 minutes (Mahmoud, F. et al, 2016). Finally, an study with oolong tea demonstrated that the consumption of 1,500 mL oolong tea [five tea bags (15 g of tea leaf) were added to 1,500 mL of boiling water and steeped for 10 minutes] taken five times per day independent of daily water intake for 30 days diminished the glycaemia and plasma fructosamine levels (Hosoda, K. et al, 2003).…”
Section: 1-teamentioning
confidence: 99%
“…The major contribution of the health-promoting effects of green tea is associated with its polyphenol content (Sano et al, 2001). Enhancement of immune system function (Khan et al, 2016), antibacterial activity (Di Vito et al, 2015), antineoplastic (Fujiki et al, 2015;Pedro et al, 2016), anti-inflammatory (Dona et al, 2003), antioxidative (Osada et al, 2001), antihyperlipidemic potentials (Raederstorff et al, 2003;Mahmoud et al, 2016), and protective effect over cardiovascular disease (Sueoka et al, 2001) are some of the health benefits of consuming green tea. Also green tea has been considered as a thermogenic plant for weight loss (Stohs and Badmaev, 2016).…”
Section: Introductionmentioning
confidence: 99%